2017
DOI: 10.1186/s13046-017-0582-5
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of miR-493 increases the resistance to cisplatin in lung cancer by targeting tongue cancer resistance-related protein 1(TCRP1)

Abstract: BackgroundThe potential mechanisms regarding how methylation of microRNA(miRNA) CpG Island could regulate cancer cell chemo-resistance remains unclear. This study aims to explore the epigenetic dysregulation mechanism of miRNA-493 and the ability to modulate lung cancer cell chemotherapy resistance.MethodsReal-time quantitative PCR (qRT-PCR) and In situ hybridization (ISH) were used to analyze the expression of miR-493 in lung cancer cell lines and tumor tissue, respectively. Bisulfite sequencing PCR (BSP) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 31 publications
0
26
0
Order By: Relevance
“…Notably, this second work reported that miR‐493‐5p suppressed the migration of hepatic cancer cells by negatively regulating the expression of vesicle‐associated membrane protein 2 ( VAMP2 ), an oncogenic protein. The tumor suppressor role of miR‐493‐5p has been described in other types of solid tumors . We previously characterized miR‐493‐5p anticancer activity and described a miRNA‐dependent regulatory mechanism between two distinct imprinted loci: (i) the MEG3 ‐miR‐493 locus, which was found to be epigenetically silenced by MEG3 ‐differentially regulated region hypermethylation in liver cancer cell lines and hepatic tumors from patients; and (ii) the IGF2 ‐miR‐483 locus, which was found to be overexpressed in hepatic cancer cells exhibiting IGF2 loss of imprinting .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Notably, this second work reported that miR‐493‐5p suppressed the migration of hepatic cancer cells by negatively regulating the expression of vesicle‐associated membrane protein 2 ( VAMP2 ), an oncogenic protein. The tumor suppressor role of miR‐493‐5p has been described in other types of solid tumors . We previously characterized miR‐493‐5p anticancer activity and described a miRNA‐dependent regulatory mechanism between two distinct imprinted loci: (i) the MEG3 ‐miR‐493 locus, which was found to be epigenetically silenced by MEG3 ‐differentially regulated region hypermethylation in liver cancer cell lines and hepatic tumors from patients; and (ii) the IGF2 ‐miR‐483 locus, which was found to be overexpressed in hepatic cancer cells exhibiting IGF2 loss of imprinting .…”
Section: Discussionmentioning
confidence: 97%
“…The tumor suppressor role of miR-493-5p has been described in other types of solid tumors. [26][27][28][29][30] We previously characterized miR-493-5p anticancer activity and described a miRNA-dependent regulatory mechanism between two distinct imprinted loci: (i) the MEG3-miR-493 locus, which was found to be epigenetically silenced by MEG3-differentially regulated region hypermethylation in liver cancer cell lines and hepatic tumors from patients; and (ii) the IGF2-miR-483 locus, which was found to be overexpressed in hepatic cancer cells exhibiting IGF2 loss of imprinting. 17 In addition, we reported the epigenetic silencing of miR-148a and miR-122, 2 other major tumor suppressor miRNAs, through CpG hypermethylation in HCC cells and tissues.…”
Section: Hep3b Hep3b Hepg2mentioning
confidence: 99%
“…5A). Moreover, we screened literatures relevant to miR-493-3p targeted genes in the PubMed, and indenti ed 13 target genes of miR-493-3P including: AKT2, STK38L, HMGA2, E2F5, ETS1, FAM168A, PHLPP2, RSPO2, SP1, ANTXR1, STMN-1, KCNH2, ZFX [19][20][21][26][27][28][29][30]. Ultimately, a total of 46 potential target genes of miR-493-3p were identi ed for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…However, other studies reported that up-regulated expression of miR-493-3p portend a poor prognosis [25]. Likewise, previous researches have showed silencing miR-493-3p expression increases the chemotherapy resistance in lung cancer [26]. However, the expression and speci c role of miR-493-3p, as well as clinical parameters in NSCLC has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 96%
“…10 MicroRNAs (miRNAs) are a family of small, noncoding RNA molecules that play important roles in multiple biological processes, including cell proliferation, apoptosis and organ development, in different cancers. 11 A large body of evidence suggests that miRNAs are closely associated with the development of chemoresistance in cancer cells, [12][13][14][15][16][17] indicating that miRNAs might be potential targets for cancer treatment. Previous studies showed that miR-107 expression is significantly higher in gastric cancer tissues than in adjacent normal tissues, and downregulation of miR-107 expression suppresses tumour cell proliferation, migration and invasion.…”
Section: Introductionmentioning
confidence: 99%